A COMPARATIVE ANALYSIS OF FREE SCHOOL LUNCH GOVERNANCE IN SELECTED COUNTRIES TO PREPARE A SUPERIOR GENERATION - Teguh Yuwono; K.P. Suharyono S. Hadiningrat; Novia Dwi Anggraeni; Febri Pramudya Wardani; Verry A.J.M. Silalahi (Yayasan Inspirasi Merah Putih Indonesia, 2026)
Free school lunch programs in several countries are generally intended to meet the balanced nutritional needs of beneficiaries while improving health and educational quality to prepare a superior generation. This study employed a descriptive qualitative design with a thematic narrative approach and content analysis to identify and describe phenomena based on the research variables. The study concludes that the governance of free nutritious meal programs across countries shares several common features, while also differing according to each country’s circumstances. A particularly important finding is that several developed countries have enacted statutory frameworks to ensure the continuity of these programs.